Some contemporary Ukrainian views on urbanonymic problem (pre-modern period) - Долинська, Мар'яна (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2019)
Historians insist that names of places (urbanonyms) are historical sources. There were no description of the methodology and the methods of historical researching of urbanonyms. Though, some interesting publications with a lot of data on the theme in Ukraine have appeared during the last years. The scholar from Odesa (Ihor Hulianovych) published the paper about middle 19th century urbanonyms of the South Bessarabia’s towns (Ackerman, Ismail and Cilia). The author tried to use the linguistic classification of toponyms (by Natalia Podolskaya), but he described places names without this technique and ignoring facts of the historical topography. The conclusions to the article are some disappointing – the start and the finish are similar: the author concluded that the data show the same criteria  he had a priori laid down to investigate places` names in three towns. Two papers (the article by Maria Takhtaulova and Liudmyla Savchenko and Maria Takhtaulova`s thesis) from Kharkiv are dedicated to main problems of the characteristics of a complex historical study of the cities` toponymy on the example of Kharkiv. The authors have done careful and deep analysis of the genesis and development of names in the territory of modern Kharkiv, but there is some lack of a systematic approach in these publications. There is no description how to use urbanonyms (places` names of town or city) as a historical source in these article and thesis.A review of these articles shows that scholars have to agree to consider such points: The research of the historical urbanonymy is impossible without the knowledge of historical topography 2. The doubled structure of each urbanonym (a proper noun + denotatum), allowed us to receipt a town`s proper names by their denotatums (topographic terms), more precisely by using items instead of proper noun classification.In sum, it causes the proposal to classify items and draw their hierarchical graph, which should show all manner of a town`s items (natural, manmade and demarcated) and connections of their levels. As well, common terminology needs to be developed.